Biometric answers in young plants of cane sugar under the water stress and the aluminum - Ecco, Martios; Santiago, Etenaldo Felipe; Lima, Paulo Ricardo (Comunicata Scientiae, 2014)
In the sugarcane crop the initial phenological stages are critical to the development of plants dueto the influence of many stress factors. In this work are discussed the effects of hydric stress andaluminum toxicity, for the initial development of two varieties (RB855536 e RB867515). In this way,billets containing two gems (± 25 cm) were planted in polyethylene vases with soil. The levels ofwater in the soil were defined as: control (70 to 90 % of the field capacity (FC)) and hydric stress(20 to 40 % of FC). Different doses of aluminum were applied: 0, 0.2 and 0.4 mmol L-1 in the form ofAl2(SO4)3.H2O18. With exception of number of number of tillers, the fresh mass of billet for the varietyRB855536 and dry mass of billet for variety RB867515, were verified significant differences among allt